Kinship ties across the lifespan in human communities. (2nd September 2019) - Koster, Jeremy; Lukas, Dieter; Nolin, David; Power, Eleanor; Alvergne, Alexandra; Mace, Ruth; Ross, Cody T.; Kramer, Karen; Greaves, Russell; Caudell, Mark; MacFarlan, Shane; Schniter, Eric; et al.
Abstract : A hypothesis for the evolution of long post-reproductive lifespans in the human lineage involves asymmetries in relatedness between young immigrant females and the older females in their new groups. In these circumstances, inter-generational reproductive conflicts between younger and older females are predicted to resolve in favour of the younger females, who realize fewer inclusive fitness benefits from ceding reproduction to others. This conceptual model anticipates that immigrants to a community initially have few kin ties to others in the group, gradually showing greater relatedness to group members as they have descendants who remain with them in the group. We examine this prediction in a cross-cultural sample of communities, which vary in their sex-biased dispersal patterns and other aspects of social organization. Drawing on genealogical and demographic data, the analysis provides general but not comprehensive support for the prediction that average relatedness of immigrants to other group members increases as they age. In rare cases, natal members of the community also exhibit age-related increases in relatedness. We also find large variation in the proportion of female group members who are immigrants, beyond simple traditional considerations of patrilocality or matrilocality, which raises questions about the circumstances under which this hypothesis of female competition are met. We consider possible explanations for these heterogenous results, and we address methodological considerations that merit increased attention for research on kinship and reproductive conflict in human societies. This article is part of the theme issue 'The evolution of female-biased kinship in humans and other mammals'.